Criatividade e aprendizagem na educação de jovens e adultos : discussões a partir da teoria da subjetividade - Azambuja, Isabella Kessler de (2019)
This work aims to analyze how creativity is produced and expressed in the subjective productions of students of Youth and Adult Education in their learning processes. In the Knowledge State survey we did not find any work that aligned with this perspective, only approximations. The epistemological perspective that underlies the work is the Qualitative Epistemology of González Rey (1999, 2002, 2010). The discussions about subjectivity of González Rey in the Theory of Subjectivity in the cultural-historical perspective are based on bringing the individual and historical trajectory of the individual as central to the subjective production. Therefore, we understand learning as a subjective process as well; that is, linked to the student's life trajectory. Our conception of creativity is based on the discussions of Mitjáns Martinez (1997) about the subjective and personological aspects of the creative process. Therefore, the crativity is understood as a set of subjective configurations that intercede the creative action. Understanding the impact of these theoretical conceptions for the Education of Young and Adults, we discuss this modality of education in its own idiosyncratic characteristics, understanding its students as worthy of human rights (ARROYO, 2007) and their relationships with work (GONÇALVES, 2012). The research involved a fieldwork of 5 months in an EJA class, in which the researcher, in addition to participating in the context of the students, conducted interviews with 2 participants. Several research instruments were used, such as sentence completion and photographic production. These cases were analyzed through Constructive-Interpretative Methodology. The results of the research are presented in the discussion of the two cases and in an integrative analysis. The conclusions of the study show the different forms of creativity expression for each participant; while in Euthanasio he relates more to family and work, in Sédriky it‘s related to religiosity and work. Therefore, creativity does not emerge from greater cognitive conditions, but from specific contexts of life. In the two participants we perceive that the expression of creativity, in various ways, permeates the concepts of personalization of information, confrontation with the data and production of ideas of their own, with an additional tension with social subjectivity. In addition, we perceive how the relationship with third parties is important for creative action, as well as spaces for the development of their subject conditions. Finally, we perceive a lack of hierarchy between formal or informal creative processes for the participants, both of which are of great value to them because of their capacity for tension with social subjectivity.